Synthesis of size-controllable Fe3O4 magnetic submicroparticles and its biocompatible evaluation in vitro - Tian, Qing-hua; Ning, Wen-bo; Wang, Wei-jia; Yuan, Xiu-hong; Bai, Zhi-ming (Journal of Central South University, 2016)
Large scaled uniform and size-controllable magnetic submicroparticles (MSPs) were synthesized via solvothermal method with ferric chloride as iron source and sodium acetate as trapping agent. The influence of Fe 3+ and NaAc contents on the size distribution of MSPs was investigated. The structural and morphological properties of the synthesized particles were studied by scanning electron microscopy (SEM), X-ray power diffraction (XRD) and vibrating sample magnetometer (VSM). The well-dispersed MSPs with size of 100-1000 nm were obtained by simply adjusting the contents of Fe 3+ and NaAc. In addition, the hemolysis and cytotoxicity of Fe 3 O 4 MSPs, and their ability to case arrest in cell life-cycles were studied. The results indicate that larger size could lead to lower hemolysis. From MTT(3-(4,5-dimethylthuazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, the interactions between MSPs and adhesive mouse fibroblast cell line(L929) were probed. Larger size of Fe 3 O 4 MSPs demonstrates lower cell viability following an exposure to the cells.